Antibiotic consumption in the hospital during COVID-19 pandemic, distribution of bacterial agents and antimicrobial resistance: A single-center study - Hamidi, Aziz Ahmad; Yılmaz, Şerife (Journal of Surgery and Medicine, 2021)
Background/Aim: In recent years, the consumption of broad-spectrum antibiotics used in hospitals and the number of multidrug-resistant pathogens are increasing. Coronavirus disease 2019 (COVID-19) pandemic could also affect consumption of antibiotics used in the treatment of hospital-acquired infections and cause a difference antibiotic resistance rate. There is no study on whether there was a change in this trend during the COVID-19 pandemic in Turkey. Our study was conducted to determine antibiotic consumption, the distribution of bacterial agents in culture samples and changes in their antimicrobial resistance rates in our hospital during the COVID-19 pandemic. Methods: In this retrospective cohort study, January and February 2020 were defined as the pre-pandemic period (PPP), and March and April, as the pandemic period (PP). The bacterial agents isolated from blood, urine, and respiratory samples and the rates of antibiotic consumption during these periods were compared using statistical methods. Results: A total of 3,384 samples were analyzed during the PPP and 2,170 samples, during the PP. While the total bacterial agents isolated in PPP was 469, this number was 394 in PP. The isolation of Escherichia coli, Acinetobacter baumannii complex was significantly lower in the PP (P<0.001; P=0.008, respectively). Conversely, the isolation of Enterococcus spp. was higher during the PP (P<0.001). In the PP, the consumption of piperacillin-tazobactam, teicoplanin, meropenem and fluoroquinolones (ciprofloxacin, levofloxacin, and moxifloxacin) were significantly higher (P<0.001; P=0.016; P=0.016; P=0.02; P<0.001; P=0.018, respectively) while that of cefazolin was significantly lower (P<0.001). Total antibiotic consumptions during the PPP and PP were 725.8 DDD / 1000 and 811.4 DDD / 1000 inpatient days, respectively (P=0.002). Conclusions: Although bacterial agents isolated in PP were lower, antibiotics consumption was higher. The high positivity rate of Enterococcus spp. during the PP suggests that hand hygiene and contact isolation should be strictly observed, as this may be related to the inadequacy of hygiene practices.